Structure of the stigma and style in sunflower (Helianthus annuus L.) - Gotelli, Marina María (2010)
This is the first report of the ultrastructure of the stigma and style during and after anthesis in Helianthus annuus L. using light and transmission electron microscopy. The stigma is bifid with unicellular papillae. There is no secretion of lipids, carbohydrates or proteins at anthesis. The style is semisolid in the upper portion, closer to the stigma, and becomes solid below. Ultrastructural changes on cells of the stigma and the style are described. The transmitting tissue of the ovule is first evident 40 minutes after pollination and persists during the first stages of embryogenesis. Only one pollen tube per micropyle was observed growing through this tissue.